Postoperative mycotic endophthalmitis - Rensch, Florian; Schlichtenbrede, Frank; Jonas, Jost B. (Journal of cataract and refractive surgery, 2010)
We report a series of 4 patients who experienced a low-grade mycotic endophthalmitis 3 to 7 months after uneventful cataract surgery. In all patients, the capsular bag was irrigated several times and amphotericin B was instilled intraocularly as well as systemically. In the fourth patient, a pars plans vitrectomy was been performed. Microbiological examination of aqueous humor samples revealed Candida parapsilosis in 3 patients and Candida albicans in 1 patient as causative microorganisms. At follow-up examinations performed up to 12 months after the lavage, visual acuities were 0.2, 0.1, 0.1, and hand motion in the 4 patients, respectively. The main reason for the remaining reduction in visual acuity was retinal and optic nerve atrophy. The findings show that a mycotic etiology of postoperative low-grade infectious endophthalmitis should be considered.
Gesehen am 15.05.2023